2012
DOI: 10.1093/toxsci/kfs253
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Genome-wide Mapping of AHR and ARNT Binding Sites by ChIP-Seq

Abstract: The aryl hydrocarbon receptor (AHR) and AHR nuclear translocator (ARNT) activated complex regulates genes in response to the environmental contaminant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). AHR has also emerged as a potential therapeutic target for the treatment of human diseases and different cancers, including breast cancer. To better understand AHR and ARNT signaling in breast cancer cells, we used chromatin immunoprecipitation linked to high-throughput sequencing to identify AHR- and ARNT-binding site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 48 publications
10
89
0
Order By: Relevance
“…Results showing KEGG (Ogata et al, 1999;Kanehisa and Goto, 2000;Kanehisa et al, 2002) pathways that are significantly enriched in our set of DE genes are tabulated in Table 3. In agreement with Salisbury et al (2014), we find that a known 2, 3, 7, 8 tetrachlorodibenzo-p-dioxin (TCDD) pathway is enriched in the set of DE genes, namely metabolism of xenobiotics by cytochrome P450 (Dere et al, 2011;Lo and Matthews, 2012).…”
Section: Aryl Hydrocarbon Receptor Regulation In Mcf-7 Cancer Cellssupporting
confidence: 64%
“…Results showing KEGG (Ogata et al, 1999;Kanehisa and Goto, 2000;Kanehisa et al, 2002) pathways that are significantly enriched in our set of DE genes are tabulated in Table 3. In agreement with Salisbury et al (2014), we find that a known 2, 3, 7, 8 tetrachlorodibenzo-p-dioxin (TCDD) pathway is enriched in the set of DE genes, namely metabolism of xenobiotics by cytochrome P450 (Dere et al, 2011;Lo and Matthews, 2012).…”
Section: Aryl Hydrocarbon Receptor Regulation In Mcf-7 Cancer Cellssupporting
confidence: 64%
“…Accordingly, it was shown that AHR directly binds the first intron of p21 in vitro (Barnes-Ellerbe et al, 2004;Dere et al, 2011;Lo and Matthews, 2012). Importantly, despite p21 expression being upregulated, all TCDD-treated Pax3 GFP/+ embryos developed normally, suggesting that additional GRNs downstream of PAX3 are also regulating craniofacial development.…”
Section: Discussionmentioning
confidence: 99%
“…However, under hypoxic conditions, hydroxylation does not occur, stabilizing HIF1α and targeting it for translocation into the nucleus [141, 145]. HIF1ÎČ, on the other hand, is a constitutively expressed transcription factor which is involved in several other signaling pathways, most notably the detoxification of polyaromatic hydrocarbons [149]. Several hundred genes are transcriptionally regulated by HIF1.…”
Section: Major Diseases Characterized By Aberant Pyruvate Metabolismmentioning
confidence: 99%